Complex, low-intensity, individualised naturalistic developmental behavioural intervention in toddlers and pre-schoolers with autism spectrum disorder: the multicentre, observer-blind, parallel-group randomised-controlled A-FFIP trial - Freitag, Christine M.; Kirchner, Marietta; Sauer, Lukas; Kleber, Solvejg K.; Polzer, Leonie; Raji, Naisan; Lemler, Christian; Fröhlich, Ulrike; Jarczok, Tomasz; Geissler, Julia; Radtke, Franziska; Ring, Melanie; et al. (The journal of child psychology and psychiatry, 2025)
BACKGROUND: Naturalistic developmental behavioural interventions (NDBI) may improve social communication in toddlers/pre-school aged children with autism spectrum disorder (ASD). Here, we study efficacy of the low-intensity, complex NDBI 'Frankfurt Early Intervention Program for ASD' (A-FFIP) over 1 year by a confirmatory phase-III, prospective, randomised, controlled, parallel-group study with two treatment arms over four centres. - METHODS: Main inclusion criteria: ASD (DSM-5), age 24-66 months, developmental quotient >30. - INTERVENTION: Manualised A-FFIP intervention. Control intervention: Early intervention as usual (EIAU). - PRIMARY OUTCOME: Change in core ASD symptoms from baseline (T2) to immediate intervention endpoint at 12 months (T6) based on the blindly rated Brief Observation for Communication Change (BOSCC) total score. - STATISTICAL ANALYSIS: Mixed model for repeated measures with covariates baseline BOSCC-total, chronological age and centre. - RESULTS: Between July 2018 and October 2021, N = 134 children with ASD were randomly allocated to intervention (A-FFIP: n = 68, EIAU: n = 66). Groups did not differ at baseline, with a mean age of 49 (SD 10) months, a mean developmental age of 23.3 (SD 13.6) months and 26 (19.4%) females. The SARS-CoV-2 pandemic interfered severely with trial procedures. Intention-to-treat analysis in the primary analysis set, with at least one postbaseline BOSCC measure (A-FFIP n = 64, EIAU n = 60), did not find differences in the primary outcome by group (adjusted ES -0.06, 95% CI to -0.24 to 0.11). SARS-CoV2-related lockdown led to less improvement across groups. Secondary outcomes showed stronger improvements in parent-rated repetitive behaviour as well as parent- and teacher-rated executive functions for A-FFIP versus EIAU. Adverse events were comparable between groups. - CONCLUSIONS: The manualised NDBI program A-FFIP, which allows individually targeting six core basic abilities and five developmental domains related to longitudinal development in ASD, did not improve social communication, cognitive or behavioural outcomes beyond EIAU after 1 year, but may improve repetitive behaviour and executive function.